Anders Perlinge and Hans Sjögren (Eds). Biographies of the Financial World. Gidlunds Förlag, EHFF Institute for Economic and Business History Research, 2012, 221 págs., ISBN: 978-91-7844-852-4. - Blasco-Martel, Yolanda (Investigaciones de Historia Económica, 2019)
Sin resumen